IMPLEMENTASI KEBIJAKAN VAKSINASI COVID-19 DI KOTA PEKANBARU - ', Kristayani; ', Zulkarnaini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Abstract Since January 2020, Corona Virus Disease 2019 (COVID-19) has infected more than 2,245,872 people including in Indonesia. Covid-19 is very dangerous to society due to the rapid increase in people affected by Covid-19 in Indonesia, including in Pekanbaru City. The city of Pekanbaru is one of the cities with the most dense population, making it easy for this virus to spread. The high spread of Covid-19 in society has prompted the Indonesian government to issue Minister of Health Regulation Number 18 of 2021 concerning the Implementation of Vaccinations in the Context of Mitigating the Corona Virus Diease (Covid-19). This vaccination policy aims to reduce transmission, reduce morbidity and mortality, achieve group immunity in the community, protect the community from Covid-19 so that they remain socially and economically productive. In this study using qualitative methods with data collection techniques by observation, interviews, and documentation. The data were analyzed qualitatively using the theory of Yulianto Kadji policy implementation model, namely MSN- Approach (Mentaliti, System, Networking) using the system-approach indicator. The results of this study based on system-approach indicate that the implementation of the vaccination policy has been going quite well but in its implementation there are still obstacles and rejections, namely there are still elderly people who have not been vaccinated, limited vaccine stock, long queues for vaccine implementation. Keyword : Implementation, Covid-19, Vaccination, System-Approach